The Increase Voltage Effect of The Interface Bipolar Plate to Increase H2/O2 Production Volume as alternative fuel - Salamah, Khadijah Barorotus; Akbar, Abdurrahman azzam; Soegijono, Bambang; Notonegoro, Hamdan Akbar (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2023)
Renewable fuels hold the key to the increasing energy demand and environmental issues. In recent years, the installed capacity of renewable energy sources has experienced rapid growth based on limited remaining oil reserves. Applying hydrogen/oxygen as fuel in combustion engines is possible. Hydrogen (H2) which burns with Oxygen (O2) in the combustion chamber, will produce H2O compounds that are environmentally friendly. In this study, we wanted to see the effect of increasing the voltage of the interface bipolar plate to increase the H2 and O2 gas molecules volume. The experimental results show that the breaking of bonds in water compounds which utilize the interaction force between fields and charges, has been affected by an increase in voltage. The time to convert the H2O compound into H2/O2 gas molecules decreases with the increasing voltage between interfacing electrodes. The voltage increase affects the Volumetric Flow Rate (VFR) of H2 dan O2 gas molecules. This study also shows that when a voltage of 10 Volts is applied at the electrode interface, charge transport occurs optimally.